Psychometric Assessment of the Dimensional Obsessive Compulsive Scale - Short Form (DOCS-SF) - Al-Awaqleh, Momen Ali (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed at Arabizing and adapting the Dimensional Obsessive Compulsive Scale- Short Form (DOCS-SF), revealing its psychometric properties of validity as well as reliability, and examined the cut-off points of a sample of Jordanian society. Methods: The Dimensional Obsessive Compulsive Scale - Short Form (DOCS-SF) and Yale-Brown Obsessive Compulsive Scale (Y-BOCS) were applied to the study samples consisted of (89) participants, divided into two samples: The Clinical Sample diagnosed with Obsessive Compulsive Disorder of (43) and a Sample of Non-clinical (46) participants. After that, to answer the study questions, many statistical analyses were carried out. The validity indicators were examined in several ways including: Construct Validity by Internal Consistency Validity, Discriminatory Validity, and Convergent Validity was extracted by calculating the Pearson Correlation Coefficient between the Dimensional Obsessive Compulsive Scale - Short Form and the Yale-Brown Obsessive Compulsive Scale. Results: Pearson correlation coefficients between the item and the total score of the scale ranged between (.94**-.98**), while Discriminatory Validity indicated the scale’s ability to distinguish between the two samples, in addition to high Convergent Validity of (.81) with (Y- BOCS). As for reliability, it was high in two ways: Internal Consistency Method and Test Re – Test Method which reached (.93). The diagnostic cut-off points (16) of the scale were tested and indicated a match with the cut-off point extracted from the original study. Conclusions: Indicates high Psychometric Properties to measure the Dimensional Obsessive Compulsive Scale - Short Form on the Jordanian society.